Introduction to the special issue on The Beatles: Nothing you can know that isn't known?. (25th June 2015) - Collins, Marcus
Abstract : Writing on The Beatles has multiplied and diversified to an astonishing extent over the past half century. The contribution of academics to this literature has until recently been modest in volume and impact. However, multidisciplinary scholarship is now producing new insights into such subjects as The Beatles' reception and their creative and commercial collaborations. Far from there being 'Nothing you can know that isn't known' about The Beatles, scholars have much to explain regarding the band's value and meaning in the 1960s and beyond.